2020
DOI: 10.3389/fncel.2020.577525
|View full text |Cite
|
Sign up to set email alerts
|

The Parvalbumin Hypothesis of Autism Spectrum Disorder

Abstract: The prevalence of autism spectrum disorder (ASD)—a type of neurodevelopmental disorder—is increasing and is around 2% in North America, Asia, and Europe. Besides the known genetic link, environmental, epigenetic, and metabolic factors have been implicated in ASD etiology. Although highly heterogeneous at the behavioral level, ASD comprises a set of core symptoms including impaired communication and social interaction skills as well as stereotyped and repetitive behaviors. This has led to the suggestion that a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 188 publications
1
39
0
Order By: Relevance
“…Similar to observations in patients with MCT8 mutations, loss of parvalbumin expression has been observed in the brains of patients with schizophrenia and autism ( Hashimoto et al, 2003 ; Lopez-Espindola et al, 2014 ; Filice et al, 2020 ). Since these psychiatric disorders are observed in perturbation of executive functions, parvalbumin expression in the human prefrontal cortex has been preferentially analyzed accordingly.…”
Section: Involvement Of Thyroid Hormone On Parvalbumin Expressionsupporting
confidence: 78%
See 1 more Smart Citation
“…Similar to observations in patients with MCT8 mutations, loss of parvalbumin expression has been observed in the brains of patients with schizophrenia and autism ( Hashimoto et al, 2003 ; Lopez-Espindola et al, 2014 ; Filice et al, 2020 ). Since these psychiatric disorders are observed in perturbation of executive functions, parvalbumin expression in the human prefrontal cortex has been preferentially analyzed accordingly.…”
Section: Involvement Of Thyroid Hormone On Parvalbumin Expressionsupporting
confidence: 78%
“…Although there are differences in the results among studies, a decrease in parvalbumin expression in the prefrontal cortex has been confirmed in schizophrenia and autism ( Beasley and Reynolds, 1997 ; Hashemi et al, 2017 ; Ariza et al, 2018 ; Kaar et al, 2019 ) ( Table 2 ). Therefore, a parvalbumin hypothesis for developmental delay has been proposed ( Filice et al, 2020 ).…”
Section: Involvement Of Thyroid Hormone On Parvalbumin Expressionmentioning
confidence: 99%
“…While it is not conclusive whether interneuron dysfunction is the primary pathological mechanism, it motivates researchers to consider these disorders to be interneuronopathies [8,76,77]. In human research, postmortem studies have consistently reported reduced cell density of PV positive fast-spiking interneurons, one of the most major classes of interneurons [67] (Figure 1), in ASD individuals [77]. In FXS individuals, however, direct evidence is limited about interneuron phenotypes.…”
Section: Asd and Fxs Are Interneuronopathymentioning
confidence: 99%
“…Not only are the reductions in the number of cells, but also, the functional alterations in inhibitory interneurons, particularly in PV interneurons, are implicated in multiple studies in FXS animal models [77]. Early works demonstrated that, in the amygdala, there is a drastic reduction both in phasic and tonic inhibitory transmission in Fmr1 KO mice Alterations in this subclass of interneurons are consistently reported in ASD.…”
Section: Asd and Fxs Are Interneuronopathymentioning
confidence: 99%
“…Regarding (b), postmortem analyses in prefrontal cortex (Brodmann Areas: 9, 46, and 47) found a reduction in FSP+ interneurons in autistic individuals, compared to controls (Hashemi et al, 2017), although this appears to stem more from a reduction in chandelier cells (Ariza et al, 2018), as opposed to basket cells which support gamma oscillations (Buzsáki & Wang, 2012). Nonetheless, it has been hypothesized that parvalbumin expression is causally related to autism (Filice et al, 2020), and the IMF bridge can put these hypotheses into a broader metabolic context. Finally, regarding (c), autistic individuals show increased levels of circulating norepinephrine (Lam et al, 2006) and increased phasic norepinephrine activity in response to prediction errors (Palmer et al, 2017), as indexed by pupillometric measures (Laeng et al, 2012; for review, see Lawson et al, 2014;Van de Cruys et al, 2014).…”
Section: Aerobic Glycolysis and Hyper-precise Predictions In Autismmentioning
confidence: 99%